Contact with Le Corbusier. Rhapsody - Martienssen, Rex D (Transvaal, Natal and Orange Free State Provincial Institutes of South African Architects and the Chapter of South African Quantity Surveyors, 1934)
"Le Corbusier says 'state the problem clearly' and take stock of present day resources. Co-ordinate all the factors involved, material, economic, metaphysical. Solve the problem strictly in terms of these."
Keywords: Le Corbusier; Corbusierism; Wyndom Lewis; Martienssen, Rex D